Compounding Benefits of Sentinel Lymph Node Biopsy for Perineal Melanoma: A Population-Based Retrospective Cohort Analysis. (May 2020) - Patel, Ronak A.; Patel, Priyanka D.; Ashack, Kurt; Borrelli, Mimi R.; Trickey, Amber; Wan, Derrick C.
Abstract : Introduction: Sentinel lymph node biopsy (SLNB) in the treatment of melanoma is known to provide valuable prognostic information. However, there is no literature describing an overall or disease-specific survival (DDS) benefit of SLNB. In the perineum, melanoma is often more advanced at presentation with current treatment guidelines translated from nonanatomic specific melanoma. As a result, there is little understanding surrounding the role of SLNB in melanoma of the perineum. Our objective is to better understand the therapeutic benefits of SLNB in perineal melanoma. Methods: The Surveillance, Epidemiology, and End Results program is a large population-based cancer registry including survival data from millions of patients in the United States. The registry was used to generate patient data for analysis from 2004 to 2016. Inclusion criteria included melanoma of the perineum; Breslow depth of 0.80 mm or greater and less than 0.80 mm with ulceration; SLNB or no intervention; clinically negative nodal disease; and available overall survival data. Results: For 879 patients from 2004 to 2016 with perineal melanoma, significant predictors of reduced survival include older than 75 years, Clark level IV–V, Breslow depth of greater than 4.00 mm, positive ulceration status, regional and distant nodal micrometastases, and clinically positive nodes on presentation. Aggregates for overall survival (OS) and disease-specific survival (DSS) were improved with implementation of SLNB. The 5-year survival rates with SLNB versus no SLNB were 54.0% and 43.0% for OS ( P = 0.001) and 57.8% and 53.1% for DSS ( P = 0.044). Stratification by Breslow depth yielded significant OS and DSS advantage for greater than 1.00 to 2.00 mm (21.3% benefit, P =0.021, and 16.8% benefit, P = 0.044) and greater than 4.00 mm (30.3% benefit, P = 0.005, and 21.0% benefit, P = 0.007) Breslow depths. Conclusions and Relevance: Sentinel lymph node biopsy may provide therapeutic benefits in addition to prognostic information for melanoma of the perineum through an increase in 5-year OS.